2022
DOI: 10.1039/d1cc06443f
|View full text |Cite
|
Sign up to set email alerts
|

Templated synthesis of zirconium(iv)-based metal–organic layers (MOLs) with accessible chelating sites

Abstract: Metal-organic layers (MOLs) are of great interest in heterogeneous catalysis, particularly those that can accommodate extraneous metal centres. Here, we demonstrate a two-step preorganisation/delamination synthetic strategy using CuI as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This may be partly attributable to hindered rotation in the shorter linkers (lacking the phenyl spacer between the pyrazole and carboxylate donors); the importance of this was recently observed by us in Zr-based MOFs formed with L1 and L1 Me where the chelating pyrazole site was shown not to be able to switch between syn and anti conformations. 27 Additionally, and particularly for L1 Me , the lack of the phenyl spacer brings the pyrazole groups close to the MOF nodes. Given these challenges we turned our attention to a computational approach to improve our understanding of the structure metrics that might allow the target MOF to form and to obtain insight into the possible formation of a MnMOF-1 type structure for shorter and longer links.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be partly attributable to hindered rotation in the shorter linkers (lacking the phenyl spacer between the pyrazole and carboxylate donors); the importance of this was recently observed by us in Zr-based MOFs formed with L1 and L1 Me where the chelating pyrazole site was shown not to be able to switch between syn and anti conformations. 27 Additionally, and particularly for L1 Me , the lack of the phenyl spacer brings the pyrazole groups close to the MOF nodes. Given these challenges we turned our attention to a computational approach to improve our understanding of the structure metrics that might allow the target MOF to form and to obtain insight into the possible formation of a MnMOF-1 type structure for shorter and longer links.…”
Section: Resultsmentioning
confidence: 99%
“…Solvents were dried using literature procedures and degassed with Ar prior to use. The ligands bis-(4-carboxypyrazolyl)methane ( L1 ), 27 bis-[4-(4-carboxyphenyl)pyrazolyl]methane ( L2 ), 28 bis-[4-(4-carboxyphenyl)-3,5-dimethylpyrazolyl]methane ( L2 Me ), 29 bis-[4-(4-carboxyphenylethynyl)pyrazolyl]methane ( L3 ), 30 and bis-[4-(4-carboxyphenylethynyl)-3,5-dimethylpyrazolyl]methane ( L3 Me ) 30 were synthesised as previously reported. The ligands 1,1-methylenebis(3,5-dimethyl-1 H -pyrazole-4-carboxylic acid) ( L1 Me ) 31 and 1,1,2,2-tetrakis[4-(4-carboxyphenyl)pyrazolyl]ethane ( L5 ) 32 have been previously reported and were synthesised with some modifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we hypothesized that careful linker design could provide a 3D pore environment suited to stabilizing binuclear complexes. Our previous studies indicated that a tetra-carboxylate linker is required to generate a 3D MOF, as flexible ditopic pyrazole carboxylate linkers exclusively produce 2D metal–organic layers (MOLs) with Zr­(IV) . Considering these design criteria, our linker of choice was 1,1,2,2-tetrakis­[4-(4-carboxyphenyl)-1 H -pyrazol-1-yl]­ethane (L1H 4 ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies indicated that a tetracarboxylate linker is required to generate a 3D MOF, as flexible ditopic pyrazole carboxylate linkers exclusively produce 2D metal−organic layers (MOLs) with Zr(IV). 40 Considering these design criteria, our linker of choice was 1,1,2,2-tetrakis[4-(4-carboxyphenyl)-1H-pyrazol-1-yl]ethane (L1H 4 ) (Figure 2). 31 Reaction of L1H 4 with ZrCl 4 using a trifluoroacetic acid (TFA) modulator in dimethylformamide (DMF) yielded colorless octahedral crystals suitable for SCXRD (Figure S1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%